A Cohort Study of the Prognostic Impact of Exon-16 EZH2 Mutations in a Mexican-Mestizo Population of Patients with Diffuse Large B-Cell Lymphoma - Luis F. Oñate-Ocaña; Mayra Ponce-Martínez; Lucia Taja-Chayeb; Olga Gutiérrez-Hernández; Alejandro Avilés-Salas; David Cantú-; Alfonso Dueñas-González; Myrna Candelaria-Hernández (Permanyer, 2021)
Background: Novel prognostic factors in patients with diffuse large B-cell lymphoma (DLBCL) are required in the era of Rituximab. Objective: The objective of the study was to study the prognostic impact of exon-16 enhancer-of-zeste homolog-2 (EZH2) mutations in patients with DLBCL. Methods: In a cohort of patients with DLBCL treated between 2015 and 2017, we analyzed the presence of EZH2 mutations and their association with clinical response (CR), relapse, progression-free survival (PFS), and overall survival (OS). Results: A total of 198 patients were included; of them, 30 (15.2%) had mutations at codon 641, in exon 16 of EZH2. Response was achieved in 151 patients (76.3%), and 43 (21.7%) relapsed or progressed during follow-up. EZH2 mutations were associated with relapse/progression (risk ratio [RR] 1.18; 95% confidence interval [CI] 0.98-1.42; p = 0.031), while a trend for not achieving a complete response was observed (RR: 0.876; 95%CI 0.74-1.038; p = 0.071). Of note, Tyr641His and Tyr641Ser EZH2 mutations were associated with shorter PFS (hazard ratio 3.234; 95% CI 1.149-9.1; p = 0.026). Conclusion: The presence of EZH2 mutations was negatively associated with relapse/progression and showed a trend for lack of complete response. Further studies are needed to define better the prognostic significance of these mutations in Mexican-Mestizo DLBCL patients.